Cost-effectiveness of Yoga for Chronic Low Back Pain in Veterans. Issue 9 (September 2020) - Groessl, Erik J.; Liu, Lin; Richard, Erin L.; Tally, Steven R.
Abstract : Background: Yoga interventions can improve function and reduce pain in persons with chronic low back pain (cLBP). Objective: Using data from a recent trial of yoga for military veterans with cLBP, we analyzed the incremental cost-effectiveness of yoga compared with usual care. Methods: Participants (n=150) were randomized to either 2× weekly, 60-minute yoga sessions for 12 weeks, or to delayed treatment (DT). Outcomes were measured at 12 weeks, and 6 months. Quality-adjusted life years (QALYs) were measured using the EQ-5D scale. A 30% improvement on the Roland-Morris Disability Questionnaire (primary outcome) served as an additional effectiveness measure. Intervention costs including personnel, materials, and transportation were tracked during the study. Health care costs were obtained from patient medical records. Health care organization and societal perspectives were examined with a 12-month horizon. Results: Incremental QALYs gained by the yoga group over 12 months were 0.043. Intervention costs to deliver yoga were 307/participant. Negligible differences in health care costs were found between groups. From the health care organization perspective, the incremental cost-effectiveness ratio to provide yoga was 4488/QALY. From the societal perspective, yoga was "dominant" providing both health benefit and cost savings. Probabilistic sensitivity analysis indicates an 89% chance of yoga being cost-effective at a willingness-to-pay of 50, 000. A scenario comparing the costs of yoga and physical therapy suggest that yoga may produce similar results at a much lower cost. Discussion/Conclusions: Yoga is a cost-effective treatment for reducing pain and disability among military veterans with cLBP. Abstract : Supplemental Digital Content is available in the text.